Transient Multiple Removal and Subsequent Reimplantation of Abdominal and Retroperitoneal Organs with Multisystemic Neoplastic Lesions - Shcherbyuk, A.N.; Dydykin, S.S.; Zhandarov, K.A.; Gulyaev, V.A.; Bibalaev, M.H.; Kapitonova, M.Y. (Nizhny Novgorod State Medical Academy of the Ministry of Health of the Russian Federation, 2017)
The aim of the study was to develop simple, minimally invasive method of transient multiple removal and subsequent reimplantation of abdominal and retroperitoneal organs with multisystemic neoplastic lesions, allowing subsequent reimplantation of the organ block after extracorporeal surgery.